Effect of point of care blood testing on physical health check completion in mental health services: mixed-methods evaluation. Issue 6 (27th October 2020) - Butler, Joseph; de Cassan, Simone; Glogowska, Margaret; Fanshawe, Thomas R.; Turner, Phil; Walton, Debbie; Lasserson, Daniel; Bale, Robert; Lennox, Belinda; Hayward, Gail
Abstract : Background: Physical health outcomes in severe mental illness are worse than in the general population. Routine physical health check completion in this group is poor. Aims: To quantitatively and qualitatively evaluate the impact of point of care (POC) blood testing on physical health check completion in community mental health services. Method: In a prospective cohort design, we equipped an early intervention service (EIS) and a community mental health team (CMHT) with a POC blood testing device for 6 months. We compared rates of blood test and full physical health check completion in the intervention teams with a matched EIS and CMHT, historically and during the intervention. We explored attitudes to POC testing using thematic analysis of semi-structured interviews with patients and clinicians. Results: Although the CMHT scarcely used the POC device and saw no change in outcomes, direct comparison of testing rates in the intervention period showed increased physical health check completion in the EIS with the device (rate ratio RR = 5.18; 95% CI 2.54–12.44; P < 0.001) compared with usual care. The rate was consistent with the EIS's increasing rate of testing over time (RR = 0.45; 95% 0.09–2.08; P = 0.32). Similar trends were seen in blood test completion. POC testing was acceptable to patients but clinicians reported usability, provision and impact on the therapeutic relationship as barriers to uptake. Conclusions: POC testing was beneficial and acceptable to patients and may increase physical health check uptake. Further research, accounting for clinician barriers, is needed to evaluate its clinical and cost-effectiveness.